A detailed insight on fabricated porous chitosan in eliminating synthetic anionic dyes from single and multi-adsorptive systems with related studies. (October 2021) - Patra, Chandi; Suganya, E.; Sivaprakasam, Senthilkumar; Krishnamoorthy, G.; Narayanasamy, Selvaraju
Abstract: Chitosan was fabricated via gelation method using CaBr2 .xH2 O/methanol solution and was studied as a potential adsorbent (MCh) in adsorbing anionic synthetic dyes like Bromophenol blue (BB), Direct blue 6 (DB) and Congo red (CR) from single (one dye species at a time) and multi (having two dyes; binary and all three dyes; tertiary) adsorptive systems. Physico-chemical modifications of MCh surface prior and post modification and dye adsorption were evaluated using scanning electron microscopy, Energy-dispersive X-ray spectroscopy, powder X-ray diffraction analysis, surface area analysis and Fourier-transformed infrared spectroscopy. Influential parameters influencing the adsorption process viz. initial pH of dye solution, MCh dosage, adsorption temperature and initial concentration of dye species were optimised. Adsorptive studies involving single adsorptive setups verified formation of sorbate's (dye species) monolayer over the sorbent's (MCh) surface via chemisorption; as established by Langmuir isotherm and pseudo-second order kinetics model analysis. Theoretical maximum adsorption capacities of MCh for BB, DB and CR was found to be 81.301 mg/g, 163.934 mg/g and 75.758 mg/g, respectively. Meanwhile, for all multi-adsorptive systems, competitive Langmuir isotherm model verified antagonistic behaviour of an individual dye over other dye adsorption over MCh surface in their respective adsorptive systems. Thermodynamics of the sorbate-sorbent interaction was exothermic, spontaneous, with elevated degree of disorderedness; concluding the interaction as thermodynamically favourable. Co-existing metal cations and anionic salts had minimal effect on MCh's adsorption efficiency. Phytotoxicity assay via germination of Vigna mungo seeds verified the efficacy of the adsorbent in eliminating the dye species from single and multi-adsorptive systems. Graphical abstract: Image 1 Highlights: Chitosan was fabricated to porous chitosan (MCh) via gelation method. Bromophenol blue, Direct blue 6 and Congo red were selected for the study. Adsorption studies were detailed using isotherm, kinetics and thermodynamics studies. Multi-adsorptive systems were studied using Competitive Langmuir adsorption isotherm. Phytotoxic assay was done using  Vigna mungo  seeds.